Sandwich Panel Manufacturing Method In Form of Test Specimens For Ship Construction - Utomo, Edy; Zubaydi, Achmad; Budipriyanto, Agung (Wave: Jurnal Ilmiah Teknologi Maritim, 2017)
Sandwich panel as a composite materials require special method of manufacture, to produce the best of physical condition. This study give the manufacturing process of sandwich panel for the purpose of testing the strength of material. Sandwich panel created with molding method for simplify the process of work and can be repeated if a failure occurs. Saveral failures occur in creating process until preparation specimen process that are influenced by saveral things, such as damage caused by the temperature of the sun, difference in viscosity between the layers of the conditions faceplate (smooth and rough), and the method of cutting the sandwich panel which requires cutting methods at low temperatures and does not produce the high vibration to avoid damage to the material before material strength test were performed.